Botswana : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that real GDP growth of Botswana slipped to an estimated 1u percent in 2001/02 (July-June), largely reflecting a downturn in the global diamond market and a drop in Botswana's diamond production. The non-mining sectors performed better, especially the service industries. Their success is in part a product of Botswana's market-friendly environment, sound macroeconomic policies, and investments in education and physical infrastructure. The overall fiscal balance moved into deficit in 2001/02 (April-March), only the second deficit in 20 years.